Protein Syndesmos is a novel RNA-binding protein that regulates primary cilia formation. Issue 22 (27th September 2018) - Avolio, Rosario; Järvelin, Aino I; Mohammed, Shabaz; Agliarulo, Ilenia; Condelli, Valentina; Zoppoli, Pietro; Calice, Giovanni; Sarnataro, Daniela; Bechara, Elias; Tartaglia, Gian G; Landriscina, Matteo; Castello, Alfredo; et al.
Abstract: Syndesmos (SDOS) is a functionally poorly characterized protein that directly interacts with p53 binding protein 1 (53BP1) and regulates its recruitment to chromatin. We show here that SDOS interacts with another important cancer-linked protein, the chaperone TRAP1, associates with actively translating polyribosomes and represses translation. Moreover, we demonstrate that SDOS directly binds RNA in living cells. Combining individual gene expression profiling, nucleotide crosslinking and immunoprecipitation (iCLIP), and ribosome profiling, we discover several crucial pathways regulated post-transcriptionally by SDOS. Among them, we identify a small subset of mRNAs responsible for the biogenesis of primary cilium that have been linked to developmental and degenerative diseases, known as ciliopathies, and cancer. We discover that SDOS binds and regulates the translation of several of these mRNAs, controlling cilia development.